2018
DOI: 10.1002/oby.22359
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Behavioral Therapy for Obesity Combined with Liraglutide 3.0 mg: A Randomized Controlled Trial

Abstract: Objective: The Centers for Medicare and Medicaid Services (CMS) covers intensive behavioral therapy (IBT) for obesity. The efficacy, however, of the specific approach has never been evaluated in a randomized trial, as described here. The 1-year trial also assessed whether the addition to IBT of liraglutide 3.0 mg would significantly increase weight loss and whether the provision of meal replacements would add further benefit. Methods: A total of 150 adults with obesity were randomly assigned to: IBT (IBT-alone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
125
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 76 publications
(136 citation statements)
references
References 39 publications
4
125
1
2
Order By: Relevance
“…This supports current practices in CBT for BED and behavioral weight management, which often address establishing regular eating patterns, controlling impulses to eat, and reducing hunger (e.g., (Murphy, Straebler, Cooper, & Fairburn, 2010;Wadden et al, 2019). This supports current practices in CBT for BED and behavioral weight management, which often address establishing regular eating patterns, controlling impulses to eat, and reducing hunger (e.g., (Murphy, Straebler, Cooper, & Fairburn, 2010;Wadden et al, 2019).…”
Section: Discussionsupporting
confidence: 67%
“…This supports current practices in CBT for BED and behavioral weight management, which often address establishing regular eating patterns, controlling impulses to eat, and reducing hunger (e.g., (Murphy, Straebler, Cooper, & Fairburn, 2010;Wadden et al, 2019). This supports current practices in CBT for BED and behavioral weight management, which often address establishing regular eating patterns, controlling impulses to eat, and reducing hunger (e.g., (Murphy, Straebler, Cooper, & Fairburn, 2010;Wadden et al, 2019).…”
Section: Discussionsupporting
confidence: 67%
“…To our knowledge, SCALE IBT represents only the second randomized controlled evaluation of the CMS‐based IBT benefit alone and combined with liraglutide 3.0 mg. The previously described trial by Wadden et al observed a significantly greater mean 1‐year weight loss of 11.5% in participants who received IBT‐liraglutide ( n = 50) compared with a loss of 6.1% for those treated with IBT alone ( n = 50). At week 24, participants in the two groups lost 10.1% and 5.4% of their baseline body weight, respectively, with 86% and 56% losing ≥ 3 kg and thus being eligible for additional IBT visits according to CMS criteria.…”
Section: Discussionmentioning
confidence: 87%
“…We are encouraged by the weight losses obtained with IBT alone in the Wadden et al study . However, the study clearly needs to be replicated to determine whether the results are generalizable beyond our single site, with its skilled interventionists and selected research participants.…”
Section: The Model Programmentioning
confidence: 96%
“…Weight losses in the Novo Nordisk‐sponsored trial compare favorably with those from the MODEL‐IBT study , the latter being expected to produce greater losses with IBT alone, given our investigative team's experience with this approach. The results achieved by the RDs in the Novo Nordisk trial are encouraging, given that some dietitians had little experience with IBT, and many of their site investigators had minimal exposure to behavioral methods of weight control.…”
Section: The Model Programmentioning
confidence: 97%
See 1 more Smart Citation